Motion and time study : design and measurement of work - Barnes, Ralph M. (Ralph Mosser), 1900- (New York : John Wiley and Sons, 1980)
Productivity. Definition and scope of motion and time study. History of motion and time study. The general problem-solving process. Work methods design-thebroad view. Work methods design-developing a better method. Process analysis. Activity charts; Man and machine charts...
Keywords: Motion study; Time study; Motion study; Time study